Recovery of walking in nonambulatory children with chronic spinal cord injuries: Case series. Issue 6 (23rd January 2023) - Howland, Dena R.; Trimble, Shelley A.; Fox, Emily J.; Tester, Nicole J.; Spiess, Martina R.; Senesac, Claudia R.; Kleim, Jeffrey A.; Spierre, Louise Z.; Rose, Dorian K.; Johns, Jeffery S.; Ugiliweneza, Beatrice; Reier, Paul J.; et al.
Abstract: The immature central nervous system is recognized as having substantial neuroplastic capacity. In this study, we explored the hypothesis that rehabilitation can exploit that potential and elicit reciprocal walking in nonambulatory children with chronic, severe (i.e., lower extremity motor score < 10/50) spinal cord injuries (SCIs). Seven male subjects (3–12 years of age) who were at least 1‐year post‐SCI and incapable of discrete leg movements believed to be required for walking, enrolled in activity‐based locomotor training (ABLT; clinicaltrials.gov NCT00488280). Six children completed the study. Following a minimum of 49 sessions of ABLT, three of the six children achieved walking with reverse rolling walkers. Stepping development, however, was not accompanied by improvement in discrete leg movements as underscored by the persistence of synergistic movements and little change in lower extremity motor scores. Interestingly, acoustic startle responses exhibited by the three responding children suggested preserved reticulospinal inputs to circuitry below the level of injury capable of mediating leg movements. On the other hand, no indication of corticospinal integrity was obtained with transcranial magnetic stimulation evoked responses in the same individuals. These findings suggest some children who are not predicted to improve motor and locomotor function may have a reserve of adaptive plasticity that can emerge in response to rehabilitative strategies such as ABLT. Further studies are warranted to determine whether a critical need exists to re‐examine rehabilitation approaches for pediatric SCI with poor prognosis for any ambulatory recovery. Abstract : Three of six children with chronic, severe spinal cord injuries and lower extremity motor scores (LEMS) ≤8/50 achieved reciprocal walking with activity‐based locomotor training. Reticulospinal tract input to the caudal spinal cord, evident by positive acoustic startle responses in lower extremity muscles was identified only in the three children who achieved walking.